The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1177/00099228211039621
|View full text |Cite
|
Sign up to set email alerts
|

Integration and Impact of Telemedicine in Underserved Pediatric Primary Care

Abstract: Telemedicine, more novel in provision of pediatric care, rapidly expanded due to the recent coronavirus disease 2019 pandemic. This study aimed to determine the feasibility of telemedicine for acute and chronic care provision in an underserved pediatric primary care center. Items assessed included patient demographic data, chief complaint, and alternative care locations if telemedicine was not available. In our setting, 62% of telemedicine visits were for acute concerns and 38% for chronic concerns. Of acute t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 29 publications
(50 reference statements)
1
20
0
1
Order By: Relevance
“…Patients and parents showed satisfaction with lifestyle changes, great enthusiasm about nutrition programs, and increased motivation [51,137]. This was reflected in increased adherence to family obesity treatment, particularly among the rural population, and in family involvement in nutrition programs [42,125].…”
Section: Before the Covid-19 Pandemicmentioning
confidence: 98%
See 4 more Smart Citations
“…Patients and parents showed satisfaction with lifestyle changes, great enthusiasm about nutrition programs, and increased motivation [51,137]. This was reflected in increased adherence to family obesity treatment, particularly among the rural population, and in family involvement in nutrition programs [42,125].…”
Section: Before the Covid-19 Pandemicmentioning
confidence: 98%
“…A study undertaken by Walters et al [42] at Cincinnati Children's Hospital evidenced that, through the provision of telemedicine, children received care in the most appropriate and cost-effective way for mild acute problems, offering the right care, at the right time, in the right place [42]. The research examined telemedicine visits during five months in the pandemic period: 62% of the visits were for acute problems, such as rash, eye drainage/redness, constipation, and cough, while 38% were for chronic conditions, in particular mental health problems (including ADHD) and asthma [42]. This study found that the implementation of telemedicine into pediatric primary care was feasible even for children from underserved communities and families reported that telemedicine provided care, guaranteeing to avoid unnecessary emergency department/urgency care visits.…”
Section: Telehealth and The Covid-19 Eramentioning
confidence: 99%
See 3 more Smart Citations